Understanding the dynamics of good neighbourliness under Rawlings and Kufuor. Issue 2 (3rd April 2018) - Asare, Bossman E.; Siaw, Emmanuel
ABSTRACT: It is widely recognised that leadership influences relations between neighbouring states in international affairs. This article seeks to further illuminate the relationship between leadership idiosyncrasies and the nature of Ghana's neighbour relations under Presidents Rawlings and Kufuor. The argument is that, while political institutionalisation and the international environment may influence neighbour relations to some degree, leader idiosyncrasy is an important intervening variable. Indeed, based on the findings, the international environment may have had less influence on Ghana's neighbour relations in the period under study (1981–2008) than conventional wisdom suggests.